2021
DOI: 10.1016/j.mvr.2021.104232
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia alters the expression of ACE2 and TMPRSS2 SARS-CoV-2 cell entry mediators in hCMEC/D3 brain endothelial cells

Abstract: The mechanisms by which the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) induces neurological complications remain to be elucidated. We aimed to identify possible effects of hypoxia on the expression of SARS-CoV-2 cell entry mediators, angiotensin-converting enzyme 2 (ACE2) receptor and transmembrane protease serine 2 (TMPRSS2) protein, in human brain endothelial cells, in vitro . hCMEC/D3 cells were exposed to different oxygen tensions: 20% (Control group), 8% or 2% O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…cells(Imperio et al, 2021). These observations are in accordance with our present data, that ACE2 is decreased while HIF-1α is increased at 24 hpi.…”
supporting
confidence: 94%
“…cells(Imperio et al, 2021). These observations are in accordance with our present data, that ACE2 is decreased while HIF-1α is increased at 24 hpi.…”
supporting
confidence: 94%
“…While viral infection may directly impact CNS cells that affect these factors, possibly by stimulating hypoxic/ischemic and hemorrhagic lesions [ 48 ], these findings may not be specific to direct viral infection on the brain since these effects could be secondary to systemic inflammation and coagulopathy caused by viral infection. In support of the possible direct effect of the virus on the brain, a few studies have shown (1) the presence of SARS-CoV-2 mRNA in cerebrospinal fluid of patients with acute COVID-19 [ 49 , 50 ], (2) the presence of ACE2 receptors in the blood–brain barrier (BBB) [ 51 , 52 ], and (3) altered BBB integrity and reduced blood flow, as well as the presence of SARS-CoV-2 in cortical neurons of patients who died of COVID-19 and immune cell infiltrates [ 48 , 53 55 ]. Since these findings have only been reported in acute stages following SARS-CoV-2 infection and given that these changes may occur either directly or indirectly, it is still unclear how viral infection impacts the brain over a longer period.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α is activated and translocated to the nucleus upon hypoxic conditions (Ke & Costa, 2006) and it has been shown that COVID-19 patients present massive hypoxia due to vasoconstriction and coagulopathy (Afsar et al, 2020). Interestingly, ACE2 expression is decreased in pulmonary smooth muscle cells upon HIF-1α accumulation (Zhang et al, 2020), whereas hypoxia leads to a biphasic modulation of both ACE2 and TMPRSS2 expression on brain microvascular endothelial cells (hCMEC/D3), with an initial increase at 6 h and a decrease at 48 h of hypoxic stimulus cells (Imperio et al, 2021). These observations are in accordance with our present data, that ACE2 is decreased while HIF-1α is increased at 24 hpi.…”
Section: Discussionmentioning
confidence: 99%